Gene expression profile of necrotizing enterocolitis model in neonatal mice. (November 2015) - Jung, Kyuwhan; Kim, Jeong-Hyun; Cheong, Hyun Sub; Shin, Eun; Kim, Seong-Ho; Hwang, Ji-Yeon; Lee, Eunyoung; Yoon, Mi-Ok; Kim, Seong-Hee; Sio, Cherry Ann; Shin, Hyoung Doo; Jung, Sung-Eun
Abstract: Background: Necrotizing enterocolitis (NEC) characterized by intestinal necrosis is one of the most common gastrointestinal emergencies in newborns. The main purpose of this study was to evaluate the whole genome expression levels in a NEC mouse model controlled with breast milk. Methods: This study induced a NEC model in mice of gestational ages of 18–21 days by intensive hypoxic insult and permitted breast-feeding instead of formula feeding. After evaluating the NEC status in the small intestines of neonatal mice by histological examination, a genome-wide gene expression profile study was completed using microarray analysis. Results: A total of 72 genes (38 down-regulated and 34 up-regulated) were observed to have significantly different expression profiles in the NEC mouse model compared with the normal control animals, based on a significance at fold change ≥ 2 and P  < 0.05. In particular, down-regulated Hist1h2aa and up-regulated Ube2i showed the most significant signals ( P  = 0.0008 for both genes). In an additional gene ontology analysis, the endopeptidase related categories (specifically, serine-type endopeptidase inhibitor activity, P  = 8.95 × 10 −5 ; P corr  = 0.008) appeared to affect NEC development in the mouse model. Conclusion: Although replications and functional evaluations are needed, our results suggest that several genes may have different expression profiles in the NEC mouse model. In particular, endopeptidase related genes (which are also known to be relevant to NEC), as identified through gene ontology analysis, may represent attractive targets for future research. Highlights: This study evaluated a gene expression profile of necrotizing enterocolitis (NEC) model in neonatal mice. Several genes were identified to have significantly different expression profiles in the NEC mouse model. Endopeptidase related categories appeared to affect NEC development in the gene ontology analysis.